Changing everyday activities and technology use in mild cognitive impairment. (February 2016) - Hedman, Annicka; Nygård, Louise; Malinowsky, Camilla; Almkvist, Ove; Kottorp, Anders
Introduction: Knowledge of the conditions under which older adults facing cognitive decline engage in everyday activities is of major importance for occupational therapists in designing supportive interventions. This study aimed to investigate perceived activity involvement over time and its longitudinal relationship to perceived ability to use everyday technology in older adults with mild cognitive impairment. Method: Thirty-seven older adults with mild cognitive impairment at inclusion were assessed over 4 years. Overall and item-specific activity involvement were analyzed using mixed-linear-effect modeling and differential item functioning. Furthermore, overall activity involvement and ability in everyday technology use were correlated. Results: Overall activity involvement decreased significantly over time. When adjusting for declining ability in the sample, actual differential item functioning indicated descending involvement in seven of 15 activities, while eight activities were stable. All leisure activities descended. The positive correlations between activity involvement and ability in everyday technology use became stronger over time. Conclusion: Variations across activities and time-points suggest that occupational therapists should repeatedly monitor the increasingly associated aspects of activity involvement and ability to use everyday technology in persons with cognitive decline.